Hepatic metastases in gastrointestinal stromal tumors: oncologic outcomes with curative-intent hepatectomy, resection of treatment-resistant disease, and tyrosine kinase inhibitor therapy alone. Issue 6 (June 2022) - Sutton, Thomas L.; Walker, Brett S.; Billingsley, Kevin G.; Sheppard, Brett C.; Corless, Christopher L.; Heinrich, Michael C.; Mayo, Skye C.
Abstract: Background: Hepatic resection for metastatic GIST (mGIST) is often performed with either curative-intent or for tyrosine kinase inhibitor (TKI)-resistant lesions. The efficacy of hepatectomy for treatment-resistant lesions (TRL) is uncertain. Methods: We reviewed patients with liver-mGIST treated from 2003 to 2018. Oncologic outcomes including overall (OS), post-operative progression-free survival (PFS), and post-progression OS were evaluated using Kaplan–Meier and Cox proportional hazards modeling. Results: We identified n = 91 patients; 31 (34%) underwent curative-intent hepatectomy, 60 (66%) were initially managed with TKI alone, and 17 (19%) had resection of a TRL. The median follow-up for resected patients was 102 months (range 5–209 months) with 23 (25%) managed with a major hepatectomy. Patients having curative-intent hepatectomy had 72% 10-year OS following diagnosis of liver-mGIST, compared with 58% ( P  = 0.50) for TRL resection and 41% ( P  = 0.01) for non-resected patients. Curative-intent hepatectomy (HR 0.39, P  = 0.03) and age (HR 1.04, P  = 0.004) were independently associated with 10-year OS, but not TRL resection. TRL resection was not associated with improved post-progression OS compared to second-line TKI therapy (HR 0.61, P  = 0.21). Conclusions: Curative-intent hepatectomy is associated with improved OS in liver-mGIST. The oncologic benefit of resecting treatment-resistant liver-mGIST compared to second-line TKI therapy alone remains unclear in the era of multi-line TKI therapy.